STRATEGI PENGEMBANGAN WAY BELERANG LAMPUNG SELATAN DENGAN PENDEKATAN AHP - Fazrin, Arick Ridho; Gunarto, Toto (Growth, 2024)
Tourism plays an important role in the regional economy, including in South Lampung Regency. Way Belerang Tourism is one of the tourist attractions that has experienced a decline in the number of visitors in recent years. This study aims to analyze the development strategy of Way Belerang tourism using the Analytical Hierarchy Process (AHP) method. This method is used to determine strategic priorities based on key factors such as facilities, promotion, attractiveness, and MSME development. Data were collected through interviews, observations, and questionnaires involving tourism stakeholders. The results of the study indicate that improving facilities and digital promotion are the main strategies in increasing the attractiveness of Way Belerang tourism. This study provides implications for local governments and tourism managers in designing sustainable destination development policies. With the implementation of the right strategy, Way Belerang has the potential to become one of the leading destinations in South Lampung.